Genetic characters of the globally spread tiger mosquito, Aedes albopictus (Diptera, Culicidae): implications from mitochondrial gene COI. Issue 1 (14th May 2018) - Ruiling, Zhang; Tongkai, Liu; Dezhen, Ma; Zhong, Zhang
ABSTRACT: There has been a rapid global expansion of Aedes albopictus, with varying biological characters and vector competence according to geographic and evolutionary origins of the invading populations. Based on mitochondrial gene cytochrome c oxidase I (COI) sequences from both native and invasive regions, genetic characters of Ae. albopictus were examined. Phylogenetic analyses indicate lineage differentiation in the original areas, and only one of the lineages was involved in the worldwide expansion. Multiple invasions were detected in populations in Africa and the Americas, whereas no obvious genetic structure was found in European populations. Asian populations showed high genetic diversity, with 42 private haplotypes being detected in this region. In addition, other genetic divergence has occurred, as in Japan and Pakistan, where populations showed significant differences from all other Asian populations. Altogether, populations in China displayed the highest genetic diversity ( Hd =0.946, π=1.609%) and significantly negative Tajima's D (−1.88475) and Fu's FS (−24.43873). This result may be attributable to the insecticide interventions used to control dengue epidemics.